2019
DOI: 10.3390/cancers11050722
|View full text |Cite
|
Sign up to set email alerts
|

POLQ Overexpression Is Associated with an Increased Somatic Mutation Load and PLK4 Overexpression in Lung Adenocarcinoma

Abstract: DNA Polymerase Theta (POLQ) is a DNA polymerase involved in error-prone translesion DNA synthesis (TLS) and error-prone repair of DNA double-strand breaks (DSBs). In the present study, we examined whether abnormal POLQ expression may be involved in the pathogenesis of lung adenocarcinoma (LAC). First, we found overexpression of POLQ at both the mRNA and protein levels in LAC, using data from the Cancer Genome Atlas (TCGA) database and by immunohistochemical analysis of our LAC series. POLQ overexpression was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…[22][23][24] In recent studies, PLK4 expression was shown to be significantly higher in malignant versus normal lungs and conferred an unfavourable survival rate, while PLK4 inhibition produces polyploidy and apoptotic death of lung cancers. 25,26 All of these results support our hypothesis that PLK4 may be a downstream target of miR-654-3p. In our study, we observed that PLK4 expression was upregulated in NSCLC tissues compared with the adjacent tissue and was negatively correlated with miR-654-3p in NSCLC patients.…”
Section: Discussionsupporting
confidence: 82%
“…[22][23][24] In recent studies, PLK4 expression was shown to be significantly higher in malignant versus normal lungs and conferred an unfavourable survival rate, while PLK4 inhibition produces polyploidy and apoptotic death of lung cancers. 25,26 All of these results support our hypothesis that PLK4 may be a downstream target of miR-654-3p. In our study, we observed that PLK4 expression was upregulated in NSCLC tissues compared with the adjacent tissue and was negatively correlated with miR-654-3p in NSCLC patients.…”
Section: Discussionsupporting
confidence: 82%
“…DNA polymerase θ (POLQ)) in tumors that induce poor OS of patients. 36,37 In contrast, in stomach cancer and colorectal cancer patients, high NEIL3 expression was associated with better cancer-specific survival. Therefore, NEIL3 overexpression may play a very different role in cancers arising from different tissues, as other studies have shown.…”
Section: Discussionmentioning
confidence: 96%
“…DNA Polymerase Theta (POLQ) is a DNA polymerase involved in translation DNA synthesis (TLS) and DNA doublestrand break (DSB) repair. Moreover, elevated expression levels of Plk4 were largely correlated with overexpression of DNA polymerase PQLQ at both mRNA and protein in LAC and coexpression of Plk4 and POLQ induced more significant centriole overduplication than the expression of either one alone, suggesting the potential cooperation of Plk4 and PQLQ in LAC oncogenesis (208).…”
Section: Plk4 and Lung Cancermentioning
confidence: 94%